Reformed Gatekeeping - Heinderyckx, François; Vos, Tim P. (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
This essay explores the state of gatekeeping theory at present. We discuss whether gatekeeping theory has a future, how gatekeeping – as it has evolved – still offers theoretical and explanatory value, and how gatekeeping must be reformed to maintain its worth and relevance. The notion is approached from its purpose, nature, temporality, agents and context. The article argues that gatekeeping theory will remain relevant pending a process of reform that must accompany that of journalism and news media.